Tanning Wastewater Treatment by Ultrafiltration: Process Efficiency and Fouling Behavior - Fu Yang; Zhengkun Huang; Jun Huang; Chongde Wu; Rongqing Zhou; Yao Jin (Membranes, 2021)
Ultrafiltration is a promising, environment-friendly alternative to the current physicochemical-based tannery wastewater treatment. In this work, ultrafiltration was employed to treat the tanning wastewater as an upstream process of the Zero Liquid Discharge (ZLD) system in the leather industry. The filtration efficiency and fouling behaviors were analyzed to assess the impact of membrane material and operating conditions (shear rate on the membrane surface and transmembrane pressure). The models of resistance-in-series, fouling propensity, and pore blocking were used to provide a comprehensive analysis of such a process. The results show that the process efficiency is strongly dependent on the operating conditions, while the membranes of either PES or PVDF showed similar filtration performance and fouling behavior. Reversible resistance was the main obstacle for such process. Cake formation was the main pore blocking mechanism during such process, which was independent on the operating conditions and membrane materials. The increase in shear rate significantly increased the steady-state permeation flux, thus, the filtration efficiency was improved, which resulted from both the reduction in reversible resistance and the slow-down of fouling layer accumulate rate. This is the first time that the fouling behaviors of tanning wastewater ultrafiltration were comprehensively evaluated, thus providing crucial guidance for further scientific investigation and industrial application.